EVALUATION OF DIGITAL HEALTH INFORMATION SYSTEMS IN THE MANAGEMENT OF MEDICAL RECORDS WITH HOT-FIT METHOD IN GENERAL HOSPITALS DHARMA YADNYA - Gusti Ayu Dhea yutrisna; I Gusti Agung Ngurah Putra Pradnyantara; Made Wahyu Aditya (LPPM Universitas Dhyana Pura, 2026)
The implementation of a digital health information system in improving the quality of hospital services, especially in the management of electronic medical records (ERM). Although it has been implemented, various obstacles are still found such as system disruptions, delays in data input, and limited user capabilities. Therefore, this study is aimed evaluate the digital health information system in medical record management using the HOT-Fit method at Dharma Yadnya General Hospital. The study method used is a qualitative descriptive study with a case study approach. Data collection was carried out through in-depth interviews. The number of Participants is 25 informants the EMR system. Out of those participants, 7 key informants were selected using a purposive sampling technique based on certain criteria, namely officers who were directly involved and had experience in using the system. The selection of informants was carried out until data saturation was achieved (data saturation), observation, and documentation of several informants involved in using the system. Data analysis was carried out by referring to the HOT-Fit model components, namely human, organizational, technological, and net benefit aspects. The results of the study showed that from the human aspect, users felt the system helped their work. From an organizational perspective, management and policy support are in place, but monitoring and evaluation are not yet optimal. From a technological perspective, the system is considered quite good, but technical challenges such as errors and downtime persist. The conclusion of this study is that the implementation of the digital health information system at Dharma Yadnya General Hospital has been quite successful, but not optimal in several HOT-Fit aspects. Improved human resource training, strengthened organizational support, and improved technological infrastructure are needed to optimize the system's benefits.